Polydopamine Modified Ceria Nanorods Alleviate Inflammation in Colitis by Scavenging ROS and Regulating Macrophage M2 Polarization - Zhang B; Li Q; Xu Q; Li B; Dong H; Mou Y (International Journal of Nanomedicine, 2023)
Bingqing Zhang,* Qiang Li,* Qinglin Xu, Baochao Li, Heng Dong, Yongbin Mou Nanjing Stomatological Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongbin Mou; Heng Dong, Nanjing Stomatological Hospital, Medical School of Nanjing University, #30 Zhongyang Road, Nanjing, 210008, People’s Republic of China, Email yongbinmou@nju.edu.cn; dongheng90@smail.nju.edu.cnBackground: Inflammatory bowel disease (IBD) is closely related to higher intracellular oxidative stress. Therefore, developing a novel method to scavenge the harmful reactive oxygen species (ROS) and alleviate colon inflammation to treat IBD is a promising strategy.Methods: CeO2@PDA-PEG (CeO2@PP) were synthesized by modifying ceria (CeO2) nanorods with polydopamine (PDA) and polyethylene glycol (PEG). The ROS scavenging ability of CeO2@PP was detected by using flow cytometry and confocal laser scanning microscope (CLSM). The anti-inflammatory ability of CeO2@PP was determined in vitro by treating lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. The biocompatibility of CeO2@PP was evaluated in vivo and in vitro. Moreover, the therapeutic effects of CeO2@PP in vivo were estimated in a dextran sulfate sodium salt (DSS)-induced colitis mouse model.Results: Physicochemical property results demonstrated that PDA and PEG modification endowed CeO2 nanorods with excellent dispersibility and colloidal stability. CeO2@PP maintained superior enzyme-like activity, including superoxide dismutase (SOD) and catalase (CAT), indicating antioxidant ability. Moreover, in vitro results showed that CeO2@PP with PDA promotes LPS-induced RAW 264.7 macrophages into M2-type polarization. In addition, in vitro and in vivo results showed that CeO2@PP have great biocompatibility and biosafety. Animal experiments have shown that CeO2@PP have excellent anti-inflammatory effects against DSS-induced colitis and effectively alleviated intestinal mucosal injury.Conclusion: The nanoplatform CeO2@PP possessed excellent antioxidant and anti-inflammatory properties for scavenging ROS and modulating macrophage polarization, which is beneficial for efficient colitis therapy.Graphical Abstract: Keywords: ceria, PDA, nanozyme, antioxidation, anti-inflammation, macrophage polarization, colitis